1988
DOI: 10.3382/ps.0670455
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Hens Fed Field Beans and Potential Relationships to Vicine Metabolism

Abstract: Field beans (faba beans, broad beans, horse beans, ackerbohnen, Vicia faba L.) depress weight of eggs when fed to laying hens. Vicine isolated from field beans has been shown to depress egg weight and hatchability when fed in large amounts. The present study was undertaken to determine the effect of using three varieties of field beans, varying in tannin and total vicines content, at 20% in breeder diets on reproductive performance of hens and associated vicine transfer from the diet to the egg. Data on egg pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Again, dietary vicine and convicine were not determined in their study. Moreover, in the absence of BCA, the role of dietary convicine through its aglucone isouramil in reducing hatchability and increasing embryo mortality was suggested by Naber et al (1988).…”
Section: Tablementioning
confidence: 99%
“…Again, dietary vicine and convicine were not determined in their study. Moreover, in the absence of BCA, the role of dietary convicine through its aglucone isouramil in reducing hatchability and increasing embryo mortality was suggested by Naber et al (1988).…”
Section: Tablementioning
confidence: 99%
“…After ingesting faba beans, individuals with a low-activity variant of glucose 6-phosphate dehydrogenase in erythrocytes suffer from favism, a life-threatening decrease in viable red blood cells [ 13 , 14 ]. The use of faba beans as animal feed is likewise limited, as this is known to impact productivity negatively, for instance, in poultry farming [ 15 ]. Contrary to this, the abundance of vicine and convicine seems to have a negligible impact on weaner pig performance, which is influenced by other antinutritional factors present in the faba beans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…VC can also have negative effects on monogastric livestock such as laying hens and broilers (Guillaume & Bellec, 1977;Halle, 2006;Larbier & Leclercq, 1994;Marquardt et al, 1981;Muduuli et al, 1982;Munduuli et al, 1981;Naber et al, 1988;Olaboro, Marquardt, Campbell, & Fröhlich, 1981;. Duc et al (1989) reported the presumably monogenetically inherited low VC (LVC) content of the genebank accession 1268(4)(1) from Radzikov (Poland), which has since been used in breeding and research.…”
Section: Introductionmentioning
confidence: 99%
“…VC can also have negative effects on monogastric livestock such as laying hens and broilers (Guillaume & Bellec, 1977; Halle, 2006; Larbier & Leclercq, 1994; Marquardt et al, 1981; Muduuli et al, 1982; Munduuli et al, 1981; Naber et al, 1988; Olaboro, Marquardt, Campbell, & Fröhlich, 1981; Olaboro, Marquardt, & Campbell, 1981).…”
Section: Introductionmentioning
confidence: 99%